The Role of Social Capital in Digital Entrepreneurship - Suhaeb, Firdaus W.; S. K, Ernawati (PINISI Discretion Review, 2025)
This article aims to analyze the role of social capital as a key driver of innovation in digital entrepreneurship. The advent of the digital era has fundamentally transformed the modern entrepreneurial landscape, with innovation playing a crucial role in determining competitive advantage and business continuity. In the era of digital entrepreneurship, social capital plays a significant role in accelerating the spread of innovative ideas, expanding access to strategic resources, and building collaborative ecosystems that support sustainable business growth. Literature analysis reveals that entrepreneurs who optimally manage digital social networks tend to be more innovative, adaptive, and highly competitive. Digital social capital has also been shown to enhance market understanding, facilitate access to new technologies, and support the formation of cross-sector and cross-geographic collaborations. In a highly dynamic digital ecosystem, trust built through online reputation, community reviews, and shared values is a key pillar in strengthening collaboration and driving innovation. Strengthening digital social capital is necessary to address a number of challenges, such as fragmented online communities, low digital literacy in marginalized areas, and the high potential for the spread of misinformation. Therefore, a synergistic role from stakeholders is needed to create a digital environment conducive to the growth of healthy social capital. Efforts such as strengthening digital incubators, educating on networking ethics, and implementing pro-community policies are strategic steps to make social capital the primary driver of inclusive and future-oriented entrepreneurial innovation.